Nationwide analysis of whole blood hemostatic resuscitation in civilian trauma. Issue 2 (August 2020) - Hanna, Kamil; Bible, Letitia; Chehab, Mohamad; Asmar, Samer; Douglas, Molly; Ditillo, Michael; Castanon, Lourdes; Tang, Andrew; Joseph, Bellal
Abstract : INTRODUCTION: Renewed interest in whole blood (WB) resuscitation in civilians has emerged following its military use. There is a paucity of data on its role in civilians where balanced component therapy (CT) resuscitation is the standard of care. The aim of this study was to assess nationwide outcomes of using WB as an adjunct to CT versus CT alone in resuscitating civilian trauma patients. METHODS: We analyzed the (2015–2016) Trauma Quality Improvement Program. We included adult (age, ≥18 years) trauma patients presenting with hemorrhagic shock and requiring at least 1 U of packed red blood cells (pRBCs) within 4 hours. Patients were stratified into WB-CT versus CT only. Primary outcomes were 24-hour and in-hospital mortality. Secondary outcomes were hospital length of stay and major complications. Hierarchical logistic regression was performed to account for clustering effect within hospitals and adjusting for patient- and hospital-level potential confounding factors. RESULTS: A total of 8, 494 patients were identified, of which 280 received WB-CT (WB, 1 [1–1]; pRBC, 16 [10–23]; FFP, 9 [6–16]; platelets, 3 [2–5]) and 8, 214 received CT only (pRBC, 15 [10–24]; FFP, 10 [6–16]; platelets, 2 [1–4]). Mean ± SD age was 34 ± 16 years, 79% were male, Injury Severity Score was 33 (24–43), and 63% had penetrating injuries. Patients who received WB-CT had a lower 24-hour mortality (17% vs. 25%; p = 0.002), in-hospital mortality (29% vs. 40%; p < 0.001), major complications (29% vs. 41%; p < 0.001), and a shorter length of stay (9 [7–12] vs. 15 [10–21]; p = 0.011). On regression analysis, WB was independently associated with reduced 24-hour mortality (odds ratio [OR], 0.78 [0.59–0.89]; p = 0.006), in-hospital mortality (OR, 0.88 [0.81–0.90]; p = 0.011), and major complications (OR, 0.92 [0.87–0.96]; p = 0.013). CONCLUSION: The use of WB as an adjunct to CT is associated with improved outcomes in resuscitation of severely injured civilian trauma patients. Further studies are required to evaluate the role of adding WB to massive transfusion protocols. LEVEL OF EVIDENCE: Therapeutic, level IV.